Knowledge Management in Information Center - Mulla, K. R.; Chandrashekara, M. (Journal of Information and Knowledge, 2006)
The article deals with human action and the information flow which shall be the two most dominant inputs to any strong development strategy. For this, the right information needs to be in the hands of the right people at the right time. The success does not rely on an individual’s knowledge, but the knowledge of the organization. Nowadays the information professionals are responsible for keeping relevant information, which supports the work of individual. There is enough scope for information professionals in all types of organizations. And also the role of library professionals in the 21st century will be challenging especially in digital and electronic information era.